The effective exchange rates of the euro - Luca Buldorini; Stelios Makrydakis; Christian Thimann (European Central Bank (ECB), 2002)
This paper details the methodological framework underlying the construction of the effective exchange rate (EER) indicators of the euro. This framework yields two sets of indicators - (i) one nominal and several real EER indices against a narrow reference group of euro area trading partners based on different price and cost deflators; and (ii) a nominal and a real EER index against a broad reference group of countries based on consumer prices. The narrow group consists of 12 industrial and newly industrialised euro area partner countries, while the broad group is made up of 38 trading partners including emerging market economies and economies in transition. In addition the paper computes national competitiveness indicators for the individual euro area participating countries. Finally, recent developments in the international price and cost competitiveness of the euro area as well as of euro area countries are briefly discussed on the basis of the constructed indices.
Keywords: 330; Euro; Wechselkurs; Kaufkraftparität; Eurozone; EU-Staaten